VD_FINDINFO Jug / 2024 / 486 vom 29. April 2024 - VD Tribunal cantonal (2024)
REJET DE LA DEMANDE, HOMICIDE PAR NÉGLIGENCE, MARCHE ARRIÈRE, POIDS LOURD, TORT MORAL | 44 al. 1 CO, 47 CO, 117 CP, 1 al. 1 LCR, 26 LCR, 31 al. 1 LCR, 36 al. 4 LCR, 1 al. 2 OCR, 17 al. 1 OCR